Law Enforcement Against Theft In Indonesia - Jumra Jumra (STIE Amkop Makassar, 2023)
The level of legal awareness of citizens and leaders plays an important role in the process of achieving the goals of national development. If the level of awareness of citizens and leaders is relatively high, the process of achieving national development goals will run smoothly and steadily. The progress of development in Indonesia today can be said to be experiencing very rapid development. This is reflected in the results of development that have been achieved and the benefits have been felt by citizens in their daily lives, as described above. The types of data are primary data and secondary data. Primary data is obtained through direct interviews with respondents who are competent in handling the offense of Ordinary Theft in Barebbo District, Bone Regency as well as the perpetrators and families of victims of the offense of Ordinary Theft in Barebbo District. Secondary data is obtained through literature from various books, legal rules, documents and other written data that are considered related to this research. The results showed that the factors causing the offense of Petty Theft in Barebbo Subdistrict, Bone Regency are 1) economic factors, 2) environmental factors, 3) educational factors and 4) geographical factors. Efforts that have been made in tackling the offense of Ordinary Theft in Barebbo District, Bone Regency, namely 1). Preventive Action, 2) Repressive Action.